386 Consent Practices in General Surgery – the Importance of the "Process"?. (28th February 2022) - Martyn, C.J.; McGowan, K.E.; Clements, J.M.; Kirk, S.
Abstract: Aim: Achieving valid informed consent is an essential component of the shared decision-making process. National guidance exists on the content of consent discussions. However, controversy exists as to when consent should be obtained. We aimed to assess consent practices in our institution. Method: A Prospective snapshot audit was conducted on consecutive general surgical patients undergoing elective surgery over a 4-week period. Information on consent discussions were obtained from electronic patient care records and from the written consent form prior to surgery. Local audit approval was granted. Results: 56 patients underwent an elective general surgical procedure in August 2021. Median age was 55. 73% (n = 41) were female. 63% of cases were for malignant disease (n = 35). All patients had capacity. 95% (n = 53) completed their consent form on the day of surgery. 54 patients had documented pre-operative consultant consultations with all patients receiving a diagnosis and discussion regarding treatment. 69% of patients underwent discussion about alternative options. Discussion about surgical risk took place in 30% of cases. Conclusions: Variation exists in pre-operative consent discussions. However, these discussions reflect consent as a "continuum" which may carry greater importance than the act of signing a consent form at an isolated time point.